Activation of raphe nuclei triggers rapid and distinct effects on parallel olfactory bulb output channels - Kapoor, Vikrant (Nat Neurosci, 2016)
The serotonergic raphe nuclei are involved in regulating brain states over time-scales of minutes and hours. We examined more rapid effects of serotonergic activation on two classes of principal neurons in the mouse olfactory bulb, mitral and tufted cells, which send olfactory information to distinct targets. Brief stimulation of the raphe nuclei led to excitation of tufted cells at rest and potentiation of their odor responses. While mitral cells at rest were also excited by raphe activation, their odor responses were bidirectionally modulated, leading to improved pattern separation of odors. In vitro whole-cell recordings revealed that specific optogenetic activation of raphe axons affected bulbar neurons through dual release of serotonin and glutamate. Therefore, the raphe nuclei, in addition to their role in neuromodulation of brain states, are also involved in fast, sub-second top-down modulation, similar to cortical feedback. This modulation can selectively and differentially sensitize or decorrelate distinct output channels.